Applying the Theory of Planned Behavior to Understand Universiti Malaya Students’ Intent to Participate in Sustainability Initiatives - Nur Ainin Sofea Mohd Huzer; Anggita Rahmi Hafsari; Zul Ilham (The Journal of Indonesia Sustainable Development Planning, 2025)
As universities increasingly implement sustainable practices, student engagement in pro-environmental behavior is crucial for establishing a lasting sustainable culture. While the Theory of Planned Behavior (TPB) is extensively utilized in environmental research, there is a gap in understanding student participation in university sustainability initiatives in Malaysia. This study aims to investigate the gap by analyzing student intention to participate, based on attitude, subjective norms, and perceived behavioral control through the Theory of Planned Behavior (TPB) framework. Data were acquired from 381 respondents via internet platforms and were then analyzed using statistical analysis. Results indicate no significant correlation between attitude and intention to participate. Nonetheless, subjective standard and perceived behavioral control substantially impacted intention. Additionally, gender and study background show a significant difference in intention. These findings indicate that the impact of society and perceived competence significantly impacts student participation, providing an opportunity for universities to focus on designing effective sustainability programs.